An economic analysis of the financial leasing industry - Tomkins, Cyril; Lowe, Julian F.; Morgan, Eleanor J. (Farnborough, Eng. : Saxon House, 1979)
Leasing has grown rapidly in recent years and is now fully established as a primary source of finance for capital investment.
Errata slip inserted.
Includes bibliographical references: p. 100.
II 18/01/2019
Loans
Keywords: Lease and rental services